Constructing healthy food names: On the sound symbolism of healthy food. (June 2021) - Motoki, Kosuke; Park, Jaewoo; Pathak, Abhishek; Spence, Charles
Highlights: We studied the role of the sound symbolism on constructing healthy food names. Phonemic sounds with higher (vs. lower) frequencies are perceived to be healthier. Higher (vs. lower) frequency sounds change the health perception of savoury food. The role of sounds is not observed in the health perception of sweet food. Abstract: The interest in healthy food has grown rapidly amongst both consumers and food manufacturers in recent years. However, which foods should be considered healthy is sometimes ambiguous. Identifying those factors that influence the perception of healthfulness is of interest both to consumers and to food manufacturers. Previous research has shown that product-intrinsic (e.g., nutrition) and product-extrinsic (e.g., the colour of the packaging) factors can shape the consumers' perception of healthy food. However, it is less clear how brand names, one of the important product-extrinsic factors, influence the perception of healthy food. Relying on the theory of sound symbolism, we investigated whether the sounds present in fictitious brand names would influence the expected healthfulness of food. Across four studies, we demonstrate that phonemic sounds with higher (vs. lower) frequencies (e.g., /f, s, i, e/ vs. /b, d, g, o, u/) are perceived to be healthier. Studies 1 and 2 demonstrate the phenomenon using general categories of "healthy" vs. "unhealthy" foods, whereas Studies 3 and 4 conceptually replicate the results using the names (or descriptions) of food products (e.g., "vegetable vs. beef sandwich") and a different study design (within-participants for Study 3 and between-participants for Study 4). We also explore the boundary conditions for this sound symbolic effect, demonstrating that higher (vs. lower) frequency sounds change the health perception of savoury food products, but not sweet ones (Studies 3 and 4). These findings provide actionable insights for those wanting to develop brand names for food products and reveal its important link with the consumers' perceptions of healthy food.